A novel hybrid piezo-pyroelectric energy harvesting device by integration of micropatterned poly (vinylidene fluoride) using MEMS techniques / Iman Aris Fadzallah - Iman Aris , Fadzallah (2024)
Energy harvesting has been utilized in autonomous power technology in recent decades. This concept involves the capturing of ambient energy, converting it into electrical energy to power small devices. This innovative approach is significant in two main areas; firstly, reduction in battery recharging or replacement costs in remote areas and secondly, elimination of the need of battery disposal which addressing the environmental concerns. Past studies have demonstrated various piezoelectric materials were utilized to scavenge many forms of ambient energy such as mechanical vibration, thermal fluctuations and solar energy for energy harvesting systems. In this thesis, we propose poly(vinylidene fluoride) PVDF-based harvesting (EH) device to harvest hybrid piezo-pyroelectric energy from wind flow generated by a hot air blower. The novelty in this work lies in the integration of micropatterned PVDF film using microelectromechanical systems (MEMS) techniques. The initial part of EH device fabrication focuses on synthesizing electrospun PVDF nanofiber mats using a one-step electrospinning process with a variation of high voltages. To characterize the electrospun PVDF films, analyses were conducted using Fourier-transform infrared (FTIR) spectroscopy, x-ray diffraction (XRD) and field emission scanning electron microscope (FESEM). Findings from these characterizations provide insights into the β-phase fractions (F(β)), degree of crystallinity (